2005
DOI: 10.1021/ja057176r
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation of Micro-/Nanocrystalline 2,5-Dimethyl-N,N‘-dicyanoquinonediimine Complexes on SiO2/Si Substrates and Multiprobe Measurement of Conduction Properties

Abstract: Multiprobe measurements were performed on tiny single crystals of DMe-DCNQI complexes prepared directly on SiO2/Si substrates. The differences in conduction properties between the micro- and nanocrystals and bulk crystals were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…They were produced under identical conditions either in air, in vacuo, or under an atmosphere of dry nitrogen. Elemental analysis (EA) of c and d indicated that they should have stoichiometries of Ag(DM) 2 and Ag(DM) 1.5 , respectively, consistent with the results of three other experiments (X-ray absorption fine structure (XAFS), 13 C NMR, and thermal analysis). Compared to the starting material a, the DM deficiency in the stoichiometry of in d and e was a result of either sublimation or combustion of the DM molecules, as observed during illumination.…”
Section: Full Papersupporting
confidence: 65%
See 2 more Smart Citations
“…They were produced under identical conditions either in air, in vacuo, or under an atmosphere of dry nitrogen. Elemental analysis (EA) of c and d indicated that they should have stoichiometries of Ag(DM) 2 and Ag(DM) 1.5 , respectively, consistent with the results of three other experiments (X-ray absorption fine structure (XAFS), 13 C NMR, and thermal analysis). Compared to the starting material a, the DM deficiency in the stoichiometry of in d and e was a result of either sublimation or combustion of the DM molecules, as observed during illumination.…”
Section: Full Papersupporting
confidence: 65%
“…By selecting the illumination conditions, the metallic conductivity of Ag(DM) 2 was transformed into either semiconductor or insulator conductivity behavior. The electrical conductivity is dependent on the p-electron density in the DM radical anion species of Ag(DM) 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…93 The same result has been reproduced by an independent group. 119 Rectifying behavior is characteristic behavior of diodes. Diodes are fundamental and thus versatile semiconductor devices.…”
mentioning
confidence: 99%
“…Previous studies of organic crystal growth using either microscale electrodes, [ 14,15 ] confi ned growth volumes, [16][17][18] or both [ 13 ] have reported materials reminiscent in shape to those produced by bulk synthesis. In the case of (TMTSF) 2 ClO 4 , the relevant morphology is rectangular as shown schematically in Figure 2 a (referred to here as type A), with the long axis of the crystal corresponding to the chain direction of the constituent molecules.…”
mentioning
confidence: 97%